If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(s + -6) = -100 Reorder the terms: 8(-6 + s) = -100 (-6 * 8 + s * 8) = -100 (-48 + 8s) = -100 Solving -48 + 8s = -100 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 8s = -100 + 48 Combine like terms: -48 + 48 = 0 0 + 8s = -100 + 48 8s = -100 + 48 Combine like terms: -100 + 48 = -52 8s = -52 Divide each side by '8'. s = -6.5 Simplifying s = -6.5
| y/-23 | | 2(x^2+4)=0 | | 2P(A)=P(B)=5/13 | | 64p=16 | | A=3(a*a)*5a+7(a*a)*2a+7 | | 2P(A)=5/13 | | -10-3x-5x=-42 | | 70=5(4i+2) | | T+32=420 | | 2*n-(n-7)=12 | | 3(t+2)=-9 | | 0.602=j-4.75 | | 3x+2(x+1)=2x+12 | | -6x+10+2x=.22 | | 4ix=6i | | 5x-2y-9z=13 | | 7k-35=24-3k | | 3Z/7-3=-2 | | 49*3-3*(12)= | | -2+6x+2x=.2 | | -45=5s | | 45=x+38 | | X-1=2x^2-x-1 | | 7x+10y=16 | | 14+7x=-21 | | 0.15-0.2x=0.3x+3 | | 5(b-2)=40 | | 4y+7=5-2y | | 9n+10+n=100 | | 9x-3=-x^2+7x | | -1+3x+6x=26 | | 23+2(5c-2)=29 |